Komparace Mezinárodních účetních standardů a národní účetní legislativy ČR - Bajbárová, Lenka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Diplomová práce se zabývá porovnáním pravidel české účetní legislativy a mezinárodních účetních standardů IAS/IFRS. Na základě znalostí těchto legislativ analyzuje principy účtování a způsoby vykazování údajů v účetních sestavách – Rozvaha a Výkaz zisku a ztráty na příkladu konkrétní společnosti a kvantifikuje rozdíly. Výpočtem vybraných poměrových ukazatelů finanční analýzy je posouzena vypovídací hodnota výkazů sestavených podle obou uvedených legislativ.

This Master´s thesis presents a comparison of the rules of Czech accounting legislation and International Accounting Standards IAS/IFRS. Based on the knowledge of these laws, the thesis analyses accounting principles and methods of data reporting in the financial reports - Balance sheet and Profit and loss account on the example of a concrete company and quantifies differences. By calculation of selected indicators of financial ratio analysis is considered the informational value of statements drawn up under the two laws.
Comparison of International Accounting Standards and the National Accounting Legislation in Czech Republic
Keywords: Mezinárodní účetní standardy IAS/IFRS; česká účetní legislativa; účetní závěrka; účetní zásady; analýza; rentabilita.; International Accounting Standards IAS/IFRS; Czech accounting legislation; Financial Statements; Accounting Principles; Analysis; Profitability.